Factors Associated with Tuberculosis and Rifampicin-Resistant Tuberculosis amongst Symptomatic Patients in India: A Retrospective Analysis - Nair, Sreenivas Achuthan (PLoS One, 2016)
BACKGROUND: Tuberculosis remains a major public health challenge for India. Various studies have documented different levels of TB and multi-drug resistant (MDR) TB among diverse groups of the population. In view of renewed targets set under the End TB strategy by 2035, there is an urgent need for TB diagnosis to be strengthened. Drawing on data from a recent, multisite study, we address key questions for TB diagnosis amongst symptomatics presenting for care: are there subgroups of patients that are more likely than others, to be positive for TB? In turn, amongst these positive cases, are there factors—apart from treatment history—that may be predictive for multi-drug resistance? METHODS: We used data from a multi-centric prospective demonstration study, conducted from March 2012 to December 2013 in 18 sub-district level TB programme units (TUs) in India and covering a population of 8.8 million. In place of standard diagnostic tests, upfront Xpert MTB/RIF testing was offered to all presumptive TB symptomatics. Here, using data from this study, we used logistic regression to identify association between risk factors and TB and Rifampicin-Resistant TB among symptomatics enrolled in the study. RESULTS: We find that male gender; history of TB treatment; and adult age compared with either children or the elderly are risk factors associated with high TB detection amongst symptomatics, across the TUs. While treatment history is found be a significant risk factor for rifampicin-resistant TB, elderly (65+ yrs) people have significantly lower risk than other age groups. However, pediatric TB cases have no less risk of rifampicin resistance as compared with adults (OR 1.23 (95% C.I. 0.85–1.76)). Similarly, risk of rifampicin resistance among both the genders was the same. These patterns applied across the study sites involved. Notably in Mumbai, amongst those patients with microbiological confirmation of TB, female patients showed a higher risk of having MDR-TB than male patients. CONCLUSION: Our results cast fresh light on the characteristics of symptomatics presenting for care who are most likely to be microbiologically positive for TB, and for rifampicin resistance. The challenges posed by TB control are complex and multifactorial: evidence from diverse sources, including retrospective studies such as that addressed here, can be invaluable in informing future strategies to accelerate declines in TB burden.